Implikasi Bioetika Teknologi Reproduksi Modern dalam Kajian Teologi Kristen - Riris Rollyna Gultom (Jurnal Kala Nea, 2026)
Modern reproductive technology advancements such as in vitro fertilization (IVF), gamete donation, surrogacy, and genetic engineering have brought significant changes to human reproduction practices, while also raising increasingly complex bioethical and theological issues.A gap in academic research is evident in the limited studies that comprehensively examine the bioethical and theological-normative dimensions when assessing the moral implications of these technologies.This study aims to analyze the bioethics of modern reproductive technologies from a theological-normative perspective and identify the ethical implications they produce.The study employs a qualitative approach with a library research design.Data is collected from various academic literature, journals, and other relevant sources, then analyzed using content analysis to examine the principles of bioethics and the theological perspectives related to modern reproductive technologies.The findings show that although these technologies offer solutions for infertile couples, there are significant ethical concerns regarding the status of embryos, clarity of lineage, and the commercialization of the human body.These findings highlight the tension between modern bioethical principles such as autonomy, beneficence, non-maleficence, andjustice, and theological values that emphasize the sanctity of life and human moral responsibility.The significance of this study lies in its effort to integrate scientific and theological approaches in developing a more comprehensive ethical framework.In conclusion, modern reproductive technologies need to be regulated within a balanced ethical framework to respect human dignity and align with theological values.